(untitled) (Texas Journal of Engineering and Technology, 2024)
The global shift towards sustainable energy has highlighted the importance of alternative energy sources in addressing environmental challenges and reducing dependence on fossil fuels. This article examines the key problems associated with the adoption and implementation of alternative energy technologies, including high initial costs, technological barriers, and regulatory challenges. It also explores potential solutions, such as government incentives, public-private partnerships, and advancements in energy storage and grid integration. The article further discusses promising proposals and modern innovative technologies that could enhance the efficiency and scalability of alternative energy systems, including solar, wind, geothermal, and bioenergy. By analyzing current trends and future prospects, the article provides a comprehensive overview of the role of alternative energy in meeting global energy needs and mitigating climate change. The findings underscore the necessity for continued innovation, supportive policies, and international collaboration to accelerate the transition to a sustainable energy future. Keywords: Alternative Energy, Renewable Energy, Sustainable Energy, Energy Innovation, Technological Barriers, Energy Policy, Solar Power, Wind Energy, Geothermal Energy, Bioenergy, Energy Storage,Grid Integration, Climate Change, Sustainable Development